Urgensi Penyuluhan Pada Masa Pandemi Bagi Kehidupan Masyarakat Di Dusun Du’uman, Waru Timur, Waru, Pamekasan - Yanto, Yanto; Jalaluddin, Moh.; Juhairiyah, Juhairiyah; Supatmi, Any Faridatus (STAI Publisistik Thawalib Jakarta, 2022)
Du'uman is one of the hamlets that has problems, including: many people get sick and die from the corona virus, frequent early marriages that cause teenagers to lose hope to continue their education to a higher level, as well as the decline in religious activities, public activities, and lack of community solidarity values. So this service program is carried out with vaccination counseling and health protocols as well as early marriage counseling. This counseling is carried out offline, namely face to face directly on the target object. In vaccination counseling carried out by the seminar method, early marriage counseling by the lecture method. The implementation of the extension program went well, although there were several obstacles faced. Support from various parties, especially from the community itself is very helpful in the smooth implementation of this outreach program. Counseling has a positive impact on society.